A new species of Ancistrotropis (leguminosae) from Parque Nacional do Caparaó (Brazil) - Da Silva Santos, Felipe; Lima Ribeiro, Carolina; Snak, Cristiane; Delgado-Salinas, Alfonso; Paganucci De Queiroz, Luciano (Phytotaxa, 2025)
The Parque Nacional do Caparaó is a region recognised for its biodiversity within the Brazilian Atlantic Forest and as an important conservation area. Within the park, a new species of Ancistrotropis was found, which we formally propose here as A. pulchra. Based on morphological data, we found sufficient evidence to classify it within the genus and to distinguish it from other known taxa of Ancistrotropis. Furthermore, we highlight the importance of conserving these areas of high endemism and the need to centralise information on the species protected within the park.